How do you solve #3(x1)+9=15#?
The similar terms on the left side of the equation can then be combined:
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 3(x1) + 9 = 15:

Distribute the 3: 3x + 3 + 9 = 15

Combine like terms: 3x + 12 = 15

Subtract 12 from both sides: 3x = 3

Divide both sides by 3: x = 1
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation (3(x  1) + 9 = 15), follow these steps:

Expand the expression inside the parentheses: [ 3(x  1) = 3x + 3 ]

Substitute the expanded expression back into the original equation: [ 3x + 3 + 9 = 15 ]

Combine like terms: [ 3x + 12 = 15 ]

Subtract 12 from both sides of the equation: [ 3x = 3 ]

Divide both sides by 3 to isolate ( x ): [ x = 1 ]
So, the solution to the equation is ( x = 1 ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
 98% accuracy study help
 Covers math, physics, chemistry, biology, and more
 Stepbystep, indepth guides
 Readily available 24/7